X-ray phase contrast imaging and diffraction in the laser-heated diamond anvil cell: A case study on the high-pressure melting of Pt - Emma Ehrenreich-Petersen; Bernhard Massani; Thea Engler; Olivia S. Pardo; Konstantin Glazyrin; Nico Giordano; Johannes Hagemann; Daniel Sneed; Timofey Fedotenko; Daniel J. Campbell; Mario Wendt; Sergej Wenz; et al. (Results in Physics)
Melting temperatures of materials at high-pressure are one of the key physical properties that can be measured. However, large discrepancies in high-pressure melt lines exist between different experimental and theoretical approaches. In this paper, we present a novel approach for melting determination at high pressure where time-resolved synchrotron X-ray phase contrast imaging is used to observe the solid to liquid phase transition in laser heated samples in the diamond anvil cell along with simultaneous X-ray diffraction. Optical radiometric temperature measurements are correlated with the observed phase boundaries determined from X-ray phase contrast images and structural information from X-ray diffraction patterns to determine the melting temperature. We benchmarked this new technique with experiments on the high-pressure melting of platinum (Pt). Our new Pt melting results are compared with several recent studies on the high pressure melt line of Pt which utilized different techniques to determine melting. The technique can readily be applied to other materials and offers great potential for the determination of accurate and precise melting temperatures.